CONTROLLING, EVALUASI, DAN MUHASABAH - Habibah; Raisha Khotimah; Fahmi Riady; Suraijiah; Rusdiana (PT. Hasba Edukasi Mandiri, 2026)
Controlling is one of the core functions of management, serving to ensure that all organizational activities align with predetermined plans and objectives. Within educational and religious institutions, controlling is not limited to technical aspects such as efficiency and effectiveness but also encompasses moral and spiritual dimensions. An evaluation approach based on muhasabah—self-reflection and accountability—offers a relevant framework, emphasizing introspection, responsibility, and awareness of entrusted duties. The integration of modern management theory with Islamic values positions controlling as a strategic instrument that not only measures quantitative achievements but also assesses the quality of ethics, honesty, and integrity. Consequently, controlling grounded in muhasabah strengthens accountability, enhances institutional quality, and fosters an organizational culture that is both competitive and character-driven.